+0  
 
0
228
1
avatar+3486 

Help.

NotSoSmart  Oct 10, 2017
 #1
avatar+90088 
+1

 

5x + 4y  =  12     (1)

3x - 3y   =  18      divide through by 3  →  x - y  =  6  ..... 

multiply through by 4 →  4x - 4y  = 24      (2)

 

Add (1)  and (2)

 

9x  =  36       divide through by 9

 

x  = 4

 

Using    x - y  =   6, we have

 

4 - y  = 6        add y to both sides, subtract 6 from both sides

 

4 - 6  = y  =  -2

 

 

cool cool cool

CPhill  Oct 10, 2017
edited by CPhill  Oct 10, 2017

40 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.